An experimental design framework for the personalization of indoor microclimates through feedback loops between responsive thermal systems and occupant biometrics. (March 2017) - Matalucci, Berardo; Phillips, Kenton; Walf, Alicia A; Dyson, Anna; Draper, Joshua
How can building technologies accommodate different and often conflicting user preferences without dissolving the social cohesiveness, intrinsic of every architectural intervention? Individual thermal comfort has often been considered a negligible sensorial experience by modern heating and cooling technologies, and is often influenced by large-group norms. Alternatively, we propose that buildings are repositories of indoor microclimates that can be realized to provide personalized comfort, to create healthier environments, and to enhance the attributes of architectural interventions into haptic dimensions. In response, the goal of this study is to characterize an experimental framework that integrates responsive thermal systems with occupants' direct and indirect experience, which includes stress response and biometric data. A computational model was used up to inform and analyze thermal perception of subjects, and later tested in a responsive physical installation. While results show that thermal comfort assessment is affected by individual differences including cognitive functions and biometrics, further computational efforts are needed to validate biometric indicators. Finally, the implications of personalized built environments are discussed with respect to future technology developments and possibilities of design driven by biometric data.